2017
DOI: 10.2147/opth.s126459
|View full text |Cite
|
Sign up to set email alerts
|

The SPARC-related modular calcium binding protein 2 (<em>SMOC2</em>) gene polymorphism in primary glaucoma: a case-control study

Abstract: Primary glaucomas are among the most common eye diseases that may potentially result in bilateral blindness. Both genetics and environmental factors are reported to be involved in the etiology of primary glaucomas. Secreted protein acidic and rich in cysteine (SPARC)-related modular calcium binding protein 2 (SMOC2) is a matricellular glycoprotein encoded by the SMOC2 gene and known to regulate the expression of extracellular matrix (ECM) proteins and matrix metalloproteinases (MMPs), which play an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The eNOS polymorphism was also found to be associated with POAG [ 58 ]. In 2017, a case-control study associated the GA genotype of the SMOC2 (G > A) polymorphism with PACG in a SA population [ 162 ]. Additionally, in 2020 a SNP in the ACVR1 gene involved in the bone morphogenic protein (BMP) signaling pathway was associated with both PACG and PXG in a SA cohort [ 152 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eNOS polymorphism was also found to be associated with POAG [ 58 ]. In 2017, a case-control study associated the GA genotype of the SMOC2 (G > A) polymorphism with PACG in a SA population [ 162 ]. Additionally, in 2020 a SNP in the ACVR1 gene involved in the bone morphogenic protein (BMP) signaling pathway was associated with both PACG and PXG in a SA cohort [ 152 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SMOC2 polymorphism has been associated with autoimmune diseases, such as generalized vitiligo and autoimmune thyroid disease 7 , 8 . Furthermore, SMOC2 (G>A) polymorphism was reported to be significantly associated with primary glaucoma 9 . Additionally, SMOC2 mutations have been identified in several dental disorders, including a severe developmental dental defect 10 and oligodontia and microdontia 11 .…”
Section: Introductionmentioning
confidence: 99%
“…14 They were found widely expressed in all kinds of glaucomatous eyes, and the overexpression of these proteins was noted to add ECM turnover. 5,15,16 Our previous study showed that the levels of matricellular proteins, including SPARC, TSP-2, and osteopontin, were significantly elevated in eyes that suffered from acute angle closure. 4 This elevation might lead to the ECM remodeling and subsequent outflow pathway occlusion.…”
Section: Discussionmentioning
confidence: 99%